DERIVATIONAL AFFIXES IN “ALICE’S ADVENTURES IN WONDERLAND” NOVEL BY LEWIS CARROLL (Karya Ilmiah Mahasiswa (KIMA), 2024)
Morphological analysis is the main areas in studying vocabulary. The objectives of this research are to find out the derivational affixes found in Alice’s Adventures in Wonderland novel by Lewis Carroll and classify the categories of the part of speech in derivational affixes found in novel Alice’s Adventures in Wonderland by Lewis Carroll. The methods used in this research is qualitative method, were the writer tries to find out derivational affixes and category part of speech in Alice’s Adventures in Wonderland novel by Lewis Carroll. The result of this research was there were 37 words with derivational prefixes and 188 words with derivational suffixes. The prefixes are re-, a-, dis-, in- im-, non-, ex-, pre-, mis-, un-, extra-, and be- with prefix re- is the most prefix. While the suffixes are -y, -ure, -ly, -al, -ity, -ate, -ment, -age, -en, -ance, -ant, -hood, -wise, -ion, -er, -able, -less, -ness, -ent, -ify, -ful, -ence, -ic, -ous, and -ice.